CEO Turnover and Retention Light: Retaining Former CEOs on the Board - EVANS, JOHN HARRY; NAGARAJAN, NANDU J.; SCHLOETZER, JASON D. (Journal of Accounting Research, 2010)
ABSTRACT Prior CEO turnover literature characterizes the board's decision as a choice between retaining versus replacing the CEO. We focus instead on the CEO's decision rights and introduce a third option in which the incumbent CEO is removed but retained on the board for an extended period, which we call Retention Light. Firms may benefit from Retention Light because former CEOs possess unique monitoring and advising abilities, but the former CEO could also exploit available decision rights for personal benefit. A Retention Light CEO's decision rights generally exceed those of CEOs who exit the firm entirely but fall short of the rights of a retained CEO. We find that when prior firm performance is better, the former CEO is more likely to be retained on the board (Retention Light) than to exit the firm. However, this relation is weaker when the CEO reaches normal retirement age at which time CEO power becomes more important. We also provide evidence on how the nature of the CEO's bargaining power varies with his personal attributes and board characteristics in its influence on the Retention Light decision. Retention Light firms are more likely than CEO‐exit firms to select a successor CEO with relatively weaker bargaining power. Finally, Retention Light involving a nonfounder CEO is negatively associated with the firm's postturnover financial performance. Overall, Retention Light is a distinct CEO turnover option that has important consequences for board decisions and firm performance.